Strategi Pengembangan Upt Benih Induk Tanaman Hias Dan Biofarmaka Dinas Tanaman Pangan Dan Hortikultura Provinsi Sumatera Utara - Maulida Lubis; Zulkarnain Lubis; Ihsan Efendi (Universitas Medan Area, 2023)
UPT Parent Seeds of Ornamental Plants and Biopharmaceuticals of North Sumatra Province acts as a plant pilot site, carries out testing/observation of new varieties, purification of regional superior varieties seeds, training of human resources, especially apprenticeships for seed breeders, and collection of germplasm sources originating from regions areas in the province of North Sumatra and from outside the province as well as from abroad. Commodities of ornamental plants and biopharmaceutical plants have strategic meaning in North Sumatra Province because ornamental plants and biopharmaceutical plants are also expected to be a prime mover in the tourism world and at the same time become leverage for increasing income and community welfare. The purpose of this study is to analyze the factors that are strengths, weaknesses, opportunities and threats to improve the development of UPT Seed Parent Ornamental Plants and Biopharmaceuticals. The strengths of the UPT BI for Ornamental Plants and Biopharmaceuticals include the development of a large area of land, the development of a seed system with good cultivation techniques (GAP), certified products at competitive prices, and the prospects for ornamental plants and biopharmaceuticals are currently quite good. This study used descriptive qualitative method. The results of the study show the weaknesses of the UPT BI for Ornamental Plants and Biopharmaceuticals, namely governance and management are not optimal, the professionalism of human resources is still very low, the UPT Seed Parent Ornamental Plants and Biopharmaceutical is still newly established so it is still not widely known by the market, the budget for UPT Seeds Parent Ornamental Plants and Biopharmaceuticals are limited because they are still centralized in the Department of Food Crops and Horticulture, North Sumatra Province. Opportunities are the momentum during the COVID-19 pandemic, making people's interest to switch to maintaining ornamental plants at home, increasing demand for biopharmaceutical plants during the pandemic, market trends that are in line with this business and disseminating information about ornamental plant and biopharmaceutical policies in the community. Meanwhile, the threat is that the demand for ornamental plants is quite high which is still seasonal/temporary, there are competitors of ornamental plant producers